2004
DOI: 10.1159/000075591
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trans Fatty Acids on Health

Abstract: The contribution of dietary trans fatty acids (TFAs) on the risk of ischemic heart disease (IHD) has recently gained further support due to the results from large, prospective, population-based studies. Compared to saturated fat, TFAs are, gram to gram, associated with a considerably (2.5- to >10-fold) higher risk increment for IHD. A negative effect on the human fetus and on newborns and an increase in colon cancer risk in adults are possible but, however, still equivocal. Recent findings justify further stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
158
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(164 citation statements)
references
References 46 publications
0
158
0
6
Order By: Relevance
“…In addition, there are concerns about recent suggestions that TFA may affect human fetal growth and infant development (Ayagari et al 1996). Also, an association exists between the prevalence of asthma and allergies in children and the risk of diabetes in adults with the intake of trans isomers (Weiland et al 1999;Stender & Dyerberg 2004).…”
mentioning
confidence: 99%
“…In addition, there are concerns about recent suggestions that TFA may affect human fetal growth and infant development (Ayagari et al 1996). Also, an association exists between the prevalence of asthma and allergies in children and the risk of diabetes in adults with the intake of trans isomers (Weiland et al 1999;Stender & Dyerberg 2004).…”
mentioning
confidence: 99%
“…The increase in triglycerides is attributed to altered fatty acid metabolism due to disruption of proper insulin signaling. A great deal of research has shown that trans fatty acids are prodiabetic and procardiovascular diseases (31). In contrast, it appears that omega-3 fatty acids may provide some protection against diabetes and cardiovascular disease (8,19).…”
mentioning
confidence: 99%
“…Dichos elementos pueden provocar cambio en ácidos grasos trans (AGT) producto de la isomerización de los ácidos grasos cis, cuya configuración se asemeja a la de los áci-dos grasos saturados (AGS) estos AGT han demostrado que producen efectos adversos sobre los lípidos sanguíneos aumentando los niveles plasmáticos de LDL-colesterol, y de la relación LDL-c/HDL-c, en mayor medida incluso que el originado por el consumo de AGS, por lo tanto han sido relacionados con riesgo de enfermedad cardiovascular (ECV) (10), que constituye un importante problema de salud, por su alta incidencia en Colombia y en el mundo (11). De otra parte, la evidencia epidemiológica ha demostrado que los ácidos grasos poliinsaturados (AGP) tienen un efecto protector sobre el desarrollo de ECV (12); sin embargo, estos tienden a oxidarse y volverse inestables a las temperaturas de fritura y terminan sumándose a los peróxidos y AGT del aceite de fritura (13).…”
Section: Introductionunclassified